Examining the Range and Scope of Artists’ Professional Practices With Individuals With Palliative Care Needs: An International, Cross-Sectional Online Survey - Lee, Jenny Baxley; McIlfatrick, Sonja; Fitzpatrick, Lisa (Frontiers in Psychology, 2021)
Internationally, it is recognized that artists facilitate arts engagement with individuals with palliative care needs. There is a gap in the literature describing the range and scope of artists’ professional practices in palliative care. The aim of this study was to examine an international range of professional practices among artists who work in palliative care including key professionals’ perceptions of these practices. An international, cross-sectional, online survey was conducted with health professionals, artists, and program coordinators with direct experience with artists working in palliative and end-of-life care. This survey was conducted as part of a larger mixed methods study. An instrument was systematically developed to examine artists’ professional practices. Descriptive statistics were reported for the total sample including frequencies, means and standard deviations and open-ended items were analyzed thematically. 101 valid surveys were analyzed. Findings outlined: 1) who delivers the arts; 2) where and with whom; and 3) practice descriptors. Themes identified from open-ended items on benefits and risks of practice revealed impacts on patients and artists alike, including: 1) enhanced well-being; 2) vulnerabilities; and 3) facilitators and barriers. Findings demonstrated a wide range of artists’ practices in palliative and end-of-life care, featuring notable consistencies in international practice worth further exploration. Ongoing and international efforts examining artists’ practices in palliative care contribute to the development of future research, policy and practice.